STIGMATISASI MAHASISWA TENTANG MARAKNYA MAHASISWA BERCADAR DI KAMPUS (Studi Kasus Pada Mahasiswa Fakultas Ilmu Sosial dan Ilmu Politik Universitas Teuku Umar Meulaboh Kabupaten Aceh Barat) - Reni Juliani (Jurnal Community, 2018)
AbstractResearch on Student Stigma About the rise of students veiling on campus (case study at the Faculty of Social Sciences and Political Science at Teuku Umar University in West Aceh District).The purpose of this study is to familiarize students with stigmatization about the rise of students hiding at Teuku Umar Meulaboh University in the West Aceh district.The nature of this research is descriptive qualitative research, where this research aims to give a true picture, and statement on stigmatization of students Faculty of Social Sciences and Political Science at the University of Teuku Umar on rampant students who veiled on their campus.Data collection in this research is done through observation, interview and documentation.The results show that the stigma of the Faculty of Social Sciences and Political Science at the University of Teuku Umar against the veiled students is very positive that the veil has nothing to do with radicalism and terrorism and they accept the presence of students veiling their campus to have.This is because the location of Teuku Umar University in Aceh, which is the area of Islamic sharia and the majority of people accept Islam.Another reason is that there is no specific regulation at Teuku Umar University on how students should apply. The students have to dress politely and neatly.Mutual respect and respect are also the main factors in the non-discrimination of university students.But some students who have veiled at the University of Teuku Umar follow the latest trends. Keywords: Stigma, Students, Veil